2021
DOI: 10.3389/fpls.2021.645218
|View full text |Cite
|
Sign up to set email alerts
|

Maize (Zea mays L.) Nucleoskeletal Proteins Regulate Nuclear Envelope Remodeling and Function in Stomatal Complex Development and Pollen Viability

Abstract: In eukaryotes, the nuclear envelope (NE) encloses chromatin and separates it from the rest of the cell. The Linker of Nucleoskeleton and Cytoskeleton (LINC) complex physically bridges across the NE, linking nuclear and cytoplasmic components. In plants, these LINC complexes are beginning to be ascribed roles in cellular and nuclear functions, including chromatin organization, regulation of nuclei shape and movement, and cell division. Homologs of core LINC components, KASH and SUN proteins, have previously bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
(80 reference statements)
2
7
0
Order By: Relevance
“…We next examined nuclear localization patterns of MpNMCP proteins by immunohistostaining, in which functional MpNMCP:2HA fusion proteins were visualized with fluorophore-conjugated anti-HA antibodies. As shown by representative images in Figure 3A, MpNMCP is preferentially localized at the nuclear periphery in vivo, which is similar to many NMCP proteins from various plants species (Ciska et al, 2013;Sakamoto and Takagi, 2013;Yang et al, 2020;McKenna et al, 2021). Besides, we found that MpNMCP proteins were not evenly distributed at the nuclear periphery but exhibited a punctate-like pattern, which was similar to that from onion (Ciska et al, 2013).…”
Section: Mpnmcp Is Localized At the Nuclear Periphery But Does Not Control Nuclear Morphologysupporting
confidence: 63%
See 2 more Smart Citations
“…We next examined nuclear localization patterns of MpNMCP proteins by immunohistostaining, in which functional MpNMCP:2HA fusion proteins were visualized with fluorophore-conjugated anti-HA antibodies. As shown by representative images in Figure 3A, MpNMCP is preferentially localized at the nuclear periphery in vivo, which is similar to many NMCP proteins from various plants species (Ciska et al, 2013;Sakamoto and Takagi, 2013;Yang et al, 2020;McKenna et al, 2021). Besides, we found that MpNMCP proteins were not evenly distributed at the nuclear periphery but exhibited a punctate-like pattern, which was similar to that from onion (Ciska et al, 2013).…”
Section: Mpnmcp Is Localized At the Nuclear Periphery But Does Not Control Nuclear Morphologysupporting
confidence: 63%
“…Additionally, overexpression of Arabidopsis CRWN1 can partially deform the nuclear envelope by forming invaginations (Goto et al, 2014). Similar effects with the maize NMCP homolog, NCH1, have also been reported recently (McKenna et al, 2021). The conserved localization of Marchantia NMCP at the NL prompted us to ask if knocking out MpCRWN would result in similar defects in nuclear morphology and whether these defects would underlie the suppressed growth phenotype seen in the Mpnmcp mutants.…”
Section: Mpnmcp Is Localized At the Nuclear Periphery But Does Not Control Nuclear Morphologysupporting
confidence: 60%
See 1 more Smart Citation
“…KAKU4), which bear no sequence homology with animal lamin proteins. These proteins are required for proper nuclear morphology (Wang et al, 2013;Goto et al, 2014;McKenna et al, 2021) and potentially interact extensively with the nuclear pore complex basket (Mermet et al, 2021) and membrane-bound inner nuclear membrane proteins to form the plant nuclear lamina. CRWNs were recently shown to also interact with histone modifiers and to be necessary for tethering chromatin to the inner nuclear membrane to suppress stress-related gene expression (Hu et al, 2019;Mikulski et al, 2019;Choi and Richards, 2020;Sakamoto et al, 2020;Wang et al, 2021).…”
Section: The Nucleoskeletonmentioning
confidence: 99%
“…For example, lamin proteins which represent the major constituents of the animal lamina have not been identified in plants (Meier et al, 2017). Instead, three types of plant-specific proteins, CROWDED NUCLEI (CRWN) or nuclear matrix constituent protein (NMCP), KAKU4 and nuclear envelope-associated proteins (NEAPs) have been suggested to function as lamin-like proteins in plants (Masuda et al, 1997;Ciska and de la Espina, 2014;Goto et al, 2014;Pawar et al, 2016;McKenna et al, 2021). Beyond its scaffolding role, the nuclear lamina is of functional importance in chromatin folding, DNA repair, and gene transcription (Burke and Stewart, 2013).…”
Section: Organisational Principles and Functions Of The Nuclear Envelopementioning
confidence: 99%